Analysis on hydraulic parameters of interconnected suspension based on fuzzy grey correlation. (2017) - Ren, Chengyuan; Li, Kai
In this paper, a 4 DOF hydraulically interconnected suspension roll frequency domain model is set up. The frequency response functions and a road surface model are set up to achieve responses such as vertical acceleration power spectral density and roll acceleration power spectral density. For the problem of the effect of hydraulic parameters on the hydraulically interconnected suspension response, a sensitivity analysis method based on fuzzy grey correlation is used and the influence degree of hydraulic parameters to vertical response and roll response is determined. The obtained results indicate that the valve connected to hydraulic chamber has a large impact on vertical vibration modal; accumulator and the valves connected to it make a large impact on roll vibration modal. This paper provides a theoretical basis for the selection of design variables in the optimisation of the suspension.